Lucky break - "Stevens, Rob" (London; Andersen Press, 2018)
"Leon's twin, Lenny, had the best imagination in the world. He could do a back flip from a standing start and tell rude jokes nonstop for hours. But a year ago Lenny died, and Leon's family hasn't been the same since. When a new boy, Arnold, starts at Leon's school, he has no idea what to think: Arnold doesn't understand jokes, sarcasm is lost on him and he can be completely blunt. Leon has never met anyone like Arnold before, and an unlikely friendship blossoms. Before long things start to get seriously bonkers, and the two boys are breaking windows, accidentally holding up a bank and getting arrested for possession and intent with a deadly baguette. But amidst all this madness, can Awkward Arnold actually help Leon to sort his life out?"--Publisher description
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Humorous fiction